2023
DOI: 10.3390/ijms24087206
|View full text |Cite
|
Sign up to set email alerts
|

NLRC5-CIITA Fusion Protein as an Effective Inducer of MHC-I Expression and Antitumor Immunity

Abstract: Aggressive tumors evade cytotoxic T lymphocytes by suppressing MHC class-I (MHC-I) expression that also compromises tumor responsiveness to immunotherapy. MHC-I defects strongly correlate to defective expression of NLRC5, the transcriptional activator of MHC-I and antigen processing genes. In poorly immunogenic B16 melanoma cells, restoring NLRC5 expression induces MHC-I and elicits antitumor immunity, raising the possibility of using NLRC5 for tumor immunotherapy. As the clinical application of NLRC5 is const… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 88 publications
0
2
0
Order By: Relevance
“…Santharam et al. ( 67 ) similarly found that EL-4 lymphoma cells overexpressing NLRC5 increase the production and repertoire of MHC-I-associated peptides. These observations align with our findings showing an increased antitumoral response to an infected cell vaccine overexpressing NLRC5.…”
Section: Discussionmentioning
confidence: 99%
“…Santharam et al. ( 67 ) similarly found that EL-4 lymphoma cells overexpressing NLRC5 increase the production and repertoire of MHC-I-associated peptides. These observations align with our findings showing an increased antitumoral response to an infected cell vaccine overexpressing NLRC5.…”
Section: Discussionmentioning
confidence: 99%
“…Regarding the potential of NLRC5 as a predictive biomarker of tumor response to ICIs, there are emerging reports connecting NLRC5 to treatment response for various cancers, 3 4 with multiple studies suggesting that the mechanism is based on tumor evasion and mediated by human leukocyte antigens (HLA) expression. 5 Additionally, the correlation between irAEs and favorable response to ICIs has been widely demonstrated, and Jiang et al recently suggested that HLA alterations are the link between the two.…”
mentioning
confidence: 99%